Poultry gut health – microbiome functions, environmental impacts, microbiome engineering and advancements in characterization technologies - Christiana Eleojo Aruwa; Charlene Pillay; Martin M. Nyaga; Saheed Sabiu (Journal of Animal Science and Biotechnology, 2021)
Abstract The gastrointestinal tract (GIT) health impacts animal productivity. The poultry microbiome has functions which range from protection against pathogens and nutrients production, to host immune system maturation. Fluctuations in the microbiome have also been linked to prevailing environmental conditions. Healthy poultry birds possess a natural resistance to infection. However, the exploration of environmental impacts and other relevant factors on poultry growth and health have been underplayed. Since good performance and growth rate are central to animal production, the host-microbiome relationship remains integral. Prior to the emergence of metagenomic techniques, conventional methods for poultry microbiome studies were used and were low-throughput and associated with insufficient genomic data and high cost of sequencing. Fortunately, the advent of high-throughput sequencing platforms have circumvented some of these shortfalls and paved the way for increased studies on the poultry gut microbiome diversity and functions. Here, we give an up-to-date review on the impact of varied environments on microbiome profile, as well as microbiome engineering and microbiome technology advancements. It is hoped that this paper will provide invaluable information that could guide and inspire further studies on the lingering pertinent questions about the poultry microbiome.